SARS-COV-2 in Type 2 Diabetic Patients: Possible Roles of Exercise Training as a Medicine - Kushkestani, Mehdi; Parvani, Mohsen; Kazemzadeh, Yaser (Current Diabetes Reviews, 2022)
SARS-COV-2 is the novel type of beta coronavirus that was first evolved in December 2019 in Wuhan, China. People with type 2 diabetes are the most vulnerable group to SARS-COV-2 and its associated complications. Many factors such as medication, pathophysiologic-induced compensatory mechanisms, and alterations in protein expression and immune system function can all contribute to severe outcomes in diabetics. In this review article, we first described the possible mechanisms of increased risk and more severe complications rate of SARS-COV-2 in diabetic patients. Secondly, we discussed the crucial role of exercise in diabetic patients in balancing the RAS system (ACE2/ACE). Finally, we examine the possible roles of acute and chronic exercise in reducing SARS-COV-2 severe outcomes in people with diabetes in accordance with the latest evidence. We concluded that regular exercise (especially moderate-intensity exercise) can play a role in immune- enhancing, anti-inflammatory, and anti-oxidant activities and can balance the ACE2/ACE ratio (decreasing ANG2 levels) in diabetic subjects.
Keywords: health